Mothers perception about breast feeding in prematures attended in the kangaroo unit of a maternity in Fortaleza – CE - Karla Maria Carneiro Rolim; Ana Ferreira Vidal; Monalisa Abrante Mariano; Antonia do Carmo Soares Campos; Mirna Albuquerque Frota (Rev Rene)
The aim of this research was to learn about the mother’s perception on the breast feeding process in premature babies attended in the Mother-Kangaroo Unit. It is a descriptive study with qualitative approach, carried out at a public maternity, in Fortaleza-CE from January to May/2007. As subjects of the research there were10 mothers who had come along with their babies. The babies were interned in the hospital Unit. We used interviews with semi-structured questions. The subject matters were the following: maternal knowledge on the premature baby, mother’s perception on the Mother-Kangaroo method, mother’s perception in breast feeding a premature baby and the satisfaction with the action. The mother-child affective bond was evidenced and, in turn, it was considered a significant factor in the recovery of the baby.